China Economic Update, October 2014 - Smits, Karlis; Goh, Chorching; Hu, Bingjie; Vashakmadze, Ikaterine; Zhao, Luan; Bahl, Roy; Qiao, Baoyun (World Bank, Beijing, 2015)
In 2014, Chinas growth continued to slow which reflected policy to put their economic growth on a more sustainable footing. While policy efforts to tighten credit growth reduce excess capacity, internalize the cost of industrial pollution, and harden local governments budget constraints accelerated. These measures will produce a much needed realignment of growth in the medium term. A week housing market continues to be a significant drag on domestic economic activity. The government has ample policy buffers to contain a disorderly adjustment in the housing market.